Psychedelic unselfing: self-transcendence and change of values in psychedelic experiences - Kähönen, Juuso (Frontiers in Psychology, 2023)
Psychedelic experiences have been shown to both facilitate (re)connection to one’s values and change values, including enhancing aesthetic appreciation, promoting pro-environmental attitudes, and encouraging prosocial behavior. This article presents an empirically informed framework of philosophical psychology to understand how self-transcendence relates to psychedelic value changes. Most of the observed psychedelic value changes are toward the self-transcendent values of Schwartz’s value theory. As psychedelics also reliably cause various self-transcendent experiences (STEs), a parsimonious hypothesis is that STEs change values toward self-transcendent values. I argue that STEs indeed can lead to value changes, and discuss the morally relevant process of self-transcendence through Iris Murdoch’s concept of “unselfing”. I argue that overt egocentric concerns easily bias one’s valuations. Unselfing reduces egocentric attributions of salience and enhances non-egocentric attention to the world, widening one’s perspective and shifting evaluation toward self-transcendent modes. Values are inherently tied to various evaluative contexts, and unselfing can attune the individual to evaluative contexts and accompanying values beyond the self. Understood this way, psychedelics can provide temporarily enhanced access to self-transcendent values and function as sources of aspiration and value change. However, contextual factors can complicate whether STEs lead to long-term changes in values. The framework is supported by various research strands establishing empirical and conceptual connections between long-term differences in egocentricity, STEs, and self-transcendent values. Furthermore, the link between unselfing and value changes is supported by phenomenological and theoretical analysis of psychedelic experiences, as well as empirical findings on their long-term effects. This article furthers understanding of psychedelic value changes and contributes to discussions on whether value changes are justified, whether they result from cultural context, and whether psychedelics could function as tools of moral neuroenhancement.